2015
DOI: 10.1111/aos.12788
|View full text |Cite
|
Sign up to set email alerts
|

Progression of visual field in patients with primary open‐angle glaucoma – ProgF study 1

Abstract: ABSTRACT.Purpose: To evaluate the visual field rate of progression of patients with treated ocular hypertension (OHT) and primary open-angle glaucoma (POAG) in clinical practice, using the mean deviation (MD) and the visual field index (VFI). Methods: Non-interventional cohort study. From a large multicentre database representative of the French population, 441 eyes of 228 patients with treated OHT or POAG followed up at least 6 years with Humphrey 24.2 Sita-Standard visual field examination at least twice a y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 21 publications
0
36
3
2
Order By: Relevance
“…8,9 In addition, the visual field index (VFI), which was introduced in 2008, 10 has gained popularity in clinics for tracking glaucoma progression. 1113 Event and trend-based progression analyses showed similar sensitivity and specificity but moderate agreement. 14 However, VF tests are difficult for some patients and are known to have increased variability, especially in patients with advanced disease.…”
Section: Introductionmentioning
confidence: 93%
“…8,9 In addition, the visual field index (VFI), which was introduced in 2008, 10 has gained popularity in clinics for tracking glaucoma progression. 1113 Event and trend-based progression analyses showed similar sensitivity and specificity but moderate agreement. 14 However, VF tests are difficult for some patients and are known to have increased variability, especially in patients with advanced disease.…”
Section: Introductionmentioning
confidence: 93%
“…However, median rates of loss of glaucoma patients in treated clinical practice vary widely among studies, ranging from -0.05dB/year to -0.62dB/year [16-19]. Others have reported average rates of VFI loss in glaucoma patients to be between -1.1 and -1.5%/year [20-22]. Placing this in perspective, rates of VF sensitivity decline due to aging have been estimated to be -0.06dB/year [23].…”
Section: Rates Of Visual Field Lossmentioning
confidence: 99%
“…Distributions of rates of loss in various studies suggest that though most do not progress very quickly, a sizeable proportion of eyes do, as reflected by the fact that the mean rates of VF loss in studies are systematically more pessimistic than medians [15-17]. The reported proportion of glaucomatous eyes progressing at faster than -1.5 dB/year have varied from 3 to 17% in some previous studies [16, 17, 19, 20, 30-35], while others found that 15-20% of eyes seem to progress at rates of VFI loss greater than 5% per year [21, 36]. Such rates of loss would lead to perimetric blindness in 20 years assuming rates of loss remain constant.…”
Section: Rates Of Visual Field Lossmentioning
confidence: 99%
“…20 The rate of change of VFI is now incorporated in the HFA’s Guided Progression Analysis software, and so it has become widely used both clinically and in recent research studies. 2123 …”
Section: Introductionmentioning
confidence: 99%